2022
DOI: 10.1029/2021gl097127
|View full text |Cite
|
Sign up to set email alerts
|

River Dune Dynamics During Low Flows

Abstract: River dunes are dynamic and periodic bedforms in sand and gravel bed rivers, which propagate in a streamwise direction. Understanding of river dune dynamics is essential for river management. Dune shape, in combination with celerity, is a proxy for sediment transport (McElroy & Mohrig, 2009;Zomer et al., 2021), which is an important quantity to calibrate morphological models. Such models can support dredging operations to enable safe navigation. Little is known about dune dynamics during low flows due to a foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Regarding dune length, however, existing scaling laws suggest that dune length scales with water depth (Yalin, 1964;Julien and Klaassen, 1995;Van Rijn, 1984c), which is not confirmed in the area subject to study. Lokin et al (2022) observed the same, based on analysis of primary dune properties in the Waal River. They suggest that during low flows, the migration of primary dunes becomes more diffusive, due to a larger influence of gravity in the erosion-deposition processes for smaller forcing from the flow.…”
Section: Primary and Secondary Dune Morphodynamicsmentioning
confidence: 57%
See 2 more Smart Citations
“…Regarding dune length, however, existing scaling laws suggest that dune length scales with water depth (Yalin, 1964;Julien and Klaassen, 1995;Van Rijn, 1984c), which is not confirmed in the area subject to study. Lokin et al (2022) observed the same, based on analysis of primary dune properties in the Waal River. They suggest that during low flows, the migration of primary dunes becomes more diffusive, due to a larger influence of gravity in the erosion-deposition processes for smaller forcing from the flow.…”
Section: Primary and Secondary Dune Morphodynamicsmentioning
confidence: 57%
“…The Waal River is the main branch of the River Rhine in the Netherlands (Figure 1), which carries a 30-year median discharge of approximately 1500 m 3 s −1 (Lokin et al, 2022). The Waal River connects the port of Rotterdam to the inland and Germany, and is subject to intensive shipping.…”
Section: Study Area and Description Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that large bedforms (Bradley & Venditti, 2019;Cisneros et al, 2020;Lokin et al, 2022) tend to exceed the roughness limit r/R ≃ H b /h > 1/7.5 explored by Gioia and Chakraborty (2006) to reproduce the pipe friction factor (assuming a preserved K41 (Frisch, 2001) inertial subrange). A range of more stringent conditions are discussed in the literature, from H b /h < 0.15 (Amir & Castro, 2011) to H b /h < 1/40 (Jiménez, 2004), for the establishment of rough wall similarity and the preservation of the canonical logarithmic region.…”
Section: Form Drag Contributionmentioning
confidence: 96%
“…These dune height relations give a fair estimation of the dune height in shallow flows, but do not reflect the dynamics and the dune shape including slope angles and variability in lengths. Also, recent studies have shown that the dune shapes found in large rivers show different behavior than in flume experiments: dune height relative to the water depth is smaller in deep flows (Bradley & Venditti, 2017), lee slopes in deep rivers tend to have small slope angles (Cisneros et al., 2020), and dune length becomes longer during low flows (Lokin et al., 2022). Until now, dune models have mainly been applied on flume conditions (Paarlberg et al., 2009; Shimizu et al., 2009) and under normal to high flows (Paarlberg et al., 2010; Van Duin et al., 2021), while application and validation for low flows are not yet present in literature.…”
Section: Introductionmentioning
confidence: 99%